Analisis Pengaruh Sistem Penyimpanan Makanan Terhadap Kualitas Produk Cookies di Pastry Departemen Shangri-La Hotel Jakarta - Prabandari, Wijayanti Dewi; Sembiring, Vienna Artina; Karunia, Gita Putri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2022)
The purpose of this study was to determine the effect of the food storage system on the quality of cookie products at the pastry department of the Shangri-La Hotel Jakarta. The type of research used is descriptive research with a quantitative approach. The research method with simple regression analysis. Data was collected by distributing questionnaires with a Likert scale. The sampling technique used was saturated sampling technique because the total population was the same as the sample size, namely 30 employees who worked at Shangri-La Hotel Jakarta, especially those in the pastry department. The results show that the storage system has a significant effect on the quality of cookie products because the cookie product storage system is one of the determining factors for the quality of food security and safety at the Shangri-La Department hotel, Jakarta. With the existence of cookie products and a proper cookie product storage system, it can guarantee that the cookie product will be more durable in accordance with the durability of the cookie product. Keywords: Food Storage System, Product Quality